Genetic diversity based on isozymic banding pattern in Heteropogon contortus - A perennial tropical forage grass - BHAT, BILAL AHMAD; ROY, AJOY KUMAR (The Indian Journal of Agricultural Sciences, 2014)
To ascertain the extent of diversity present among the different accessions of Heteropogon contortus-a perennial fodder grass, eighty-nine genotypes collected from different parts of India were compared for four enzymes, viz. peroxidase, superoxidase dismutase (SOD), glutamate oxalo-acetate transaminase (GOT) using starch gel electrophoresis and esterase using Polyacrylamide gel electrophoresis (PAGE). Biochemical markers such as isozymes are useful supplements in identifying the genetic variation in a crop. The study revealed presence of 15 peroxidase bands, 5 SOD bands, 9 esterase bands and 1 GOT band. The GOT band was monomorphic. Polymorphism was observed for all other bands indicating thereby existence of considerable genetic diversity. Frequency of bands varied widely among the genotypes. For peroxidase, band number 3 was found to be most frequent whereas, band number 2 and 14 were least frequent and observed in only 22 and 24 genotypes respectively. None of the bands were found to be species specific. For SOD, bands 1 and 5 were most frequent and observed in 80 and 83 genotypes respectively. While all the bands were represented in 11 genotypes, a single band was observed in 7 genotypes. For esterase, 9 polymorphic bands were distributed in two distinct migration zones. Zone 1 comprised of 9 bands with low mobility (rm value 0.41 to 0.49). Band no. 2, 6 and 7 were present in higher frequency, whereas bands 4 and 5 were present in only 7 and 8 genotypes respectively. For GOT, only one monomorphic band with rm value 0.65 was recorded. Clustering based on UPGMA analysis reveals that genetic diversity could not be correlated to the geographical origin of the accessions. The study indicates that considerable genetic diversity exists in the species and collection from different geographical places will help in identifying suitable species for various agro-ecological situations as suitable forage species for rangeland conditions.